Hubungan Tindakan Kesehatan Gigi Dan Mulut Pasien Terhadap Kepatuhan Dalam Menjalani Perawatan Berulang - Ahmad Mujahidin; Galih Sampoerna (Universitas Airlangga, 2018)
Background. Oral health problems in the community one of them is behavioral factors of oral hygiene. It is associated with the treatment that requires patients to make treatment stages that can’t be resolved by the operator in a single visit. Treatment done by because there are some conditions such as emergency cases, complicated and requires a lot of time. Purpose. The aim of the study was look at the relationship between dental health measures to compliance with repeated treatments. Method. This study is an observative analytical research using cross sectional design. research is divided into two parts, to find level of dental health action and Patient Compliance In Repeated Treatment. Level of oral hygiene of patients is knew by questionnaire. Compliance is measured by looking at the card status of patients. Result. Found 45.71% of respondents have a high health measures on dental health, while another 11.43% having low health measures on dental and oral health. Then there is also a health measure as much as 42.86% of patients who were. A total of 68.57% of people dutifully repeated during treatment and no patient who did not obey repeated during treatment. A total of 11 patients from 35 patient trial (31.43%) patient compliance in a state of being. Once associated with poorer spearman correlation test statistic p-value = 0.882. Conclusion. There was no significant relationship between dental health action patient on patients compliance in repeated treatments. It is seen from the p-value> 0.05 in spearmen correlation of test results.